Factors contributing to poor performance in English at ordinary level in rural schools in Umguza district. - Ncube, Cynthia S (Midlands State University, 2020)
The research study sought to find the factors contributing to poor performance in English at ordinary level in rural schools in Umguza district. Qualitative research design was used. It enabled the researcher to look at various aspects of the study in their natural setting. Purposive sampling was used to select school heads, English teachers and ordinary level pupils who participated in the study. The researcher used interview and observation guides as well as document analysis to generate data. Data generated was analysed using thematic analysis approach. Some of the factors contributing to poor performance were, pupils’ negative attitude and shortage of teaching and learning resources. Some of the recommendations were that teachers should reward pupils who speak English as a way of motivation and that schools should engage in fundraising activities to mobilise teaching and learning resources.